Reflective Reasoning in Groups - Christina Slade (Informal Logic, 1995)
The conception of reflective reasoning, like that of higher order thinking, has been informed by a Cartesian view of the self. Reflection is conceived of as a solipsistic process, in which persons consider their own thoughts in isolation. Higher order thinking has equally been represented as a single thinker considering thoughts at a meta-level. This paper proposes a different conception of reflection and higher order thinking, in which reflective dialogue is seen as the fundamental context in which reflection is possible and higher order thinking engendered. The very process of dialectic defines what it is to be reflective and to think critically. Learning to reflect alone is a consequence of internalising the discourse.